2004
DOI: 10.1007/s00281-004-0167-1
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell-mediated T cell polarization

Abstract: Effective defense against diverse types of micro-organisms that invade our body requires specialized classes of antigen-specific immune responses initiated and maintained by distinct subsets of effector CD4(+) T helper (Th) cells. Excessive or detrimental (e.g., autoimmune) responses by effector T cells are controlled by regulatory T cells. The optimal balance in the development of the different types of effector and regulatory Th cells is orchestrated by dendritic cells (DC). This review discusses the way DC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
255
1
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(269 citation statements)
references
References 139 publications
6
255
1
7
Order By: Relevance
“…ImDCs have limited capability to induce proliferation of T lymphocytes and subsequent incompetence or anergy of T cells. 19 Furthermore, imDCs can also induce allograft tolerance, suggesting a solution to allograft rejection. 20 TGF-b1 is a key factor during the differentiation of Th cells, which can upregulate Foxp3 expression in Th0 cells, driving them to differentiate into CD4 1 Foxp3 1 Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…ImDCs have limited capability to induce proliferation of T lymphocytes and subsequent incompetence or anergy of T cells. 19 Furthermore, imDCs can also induce allograft tolerance, suggesting a solution to allograft rejection. 20 TGF-b1 is a key factor during the differentiation of Th cells, which can upregulate Foxp3 expression in Th0 cells, driving them to differentiate into CD4 1 Foxp3 1 Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…44 Mature DC1 produce high levels of interleukin-12 and other TH1-polarising signals, whereas activated DC2 polarise T-cell differentiation into TH2 cells. 45 Following allogeneic SCT, donor-derived DCs are detectable as early as 7-14 days after MAC-SCT and RIC-SCT, although they do not achieve normal values even at 1 year after transplantation. [46][47][48] DC1 recovery thereby exceeds that of DC2, resulting in a significant increased DC1/DC2 ratio in comparison with normal donors.…”
Section: B and Nk Cell Reconstitutionmentioning
confidence: 99%
“…Indeed, APCs provide T cells not only with an antigenspecific stimulatory signal (ligation of TCR) and a series of costimulatory signals, but also produce cytokines that polarize T cells toward different lineages (Th1, Th2, Th17, Tr) (de Jong et al, 2005;Kapsenberg and Kalinski, 1999). Our results show that M-CSF + MOG-treated APCs produce a low level of proinflammatory cytokines IFN-γ, TNF-α and IL-12, indicating a tolerogenic APC phenotype.…”
Section: Discussionmentioning
confidence: 64%
“…Professional APCs can either promote or suppress immune responses depending on their stage of maturation or level of activation (Lee et al, 2007;Saalmüller, 2006). In mice, APCs that produce large quantities of IL-12 and IFN-γ induce Th1 responses; APCs that produce low amounts of IL-12 but a high level of MCP-1 preferentially induce Th2 responses, whereas APCs that produce a low level of IL-12 but a high level of IL-10 induce regulatory T cell (Tr) responses (de Jong et al, 2005). In addition, our laboratory found that APCs of IL-12Rβ1 −/− mice, which lack both IL-12 and IL-23 signaling, exhibit bias toward inducing Th2 response (Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%